A Prior Magazine 13. - Roelandt, Els; Roelstraete, Dieter; Van den Bossche, Phillip; Malasauskas, Raimundas; Szylak, Aneta; Josse, Beatrice; Guenin, Hélène; Wulffen, Thomas; Holmes, Brian; Laermans, Rudi; Szewczyk, Monika; Ipollito, Jon (Gent : vzw Mark, School of Arts, 2006)
Scanlan, Joe ; Dedobbeleer, Koenraad, Olowska, PaulinaWoolford, Donelle ; Mckenzie, Lucy ; Hiwa K ; Kimpe, Kris
Documenta 12, Bare Life, Modernity is our Antiquity
boek